The Effectiveness of The Combination of Ginger (Zingiber Officinale) and Pomegranate (Punica Granatum) Towards Emesis Gravidarum Reduction in First Trimester Pregnant Women - Widyaningrum, Naniek; Yuliana, Dewi; Oktasari, Masita (Poltekkes Kemenkes Tanjung Karang, 2023)
This research aims to know the effectiveness of the combination of ginger and pomegranate towards emesis gravidarum reduction in first trimester pregnant women. This research was conducted pre-experimentally with a one group pretest-posttest design. The sampling technique used purposive sampling based on the exclusion and inclusion parameters. The research instrument used a 24-hour Pregnancy Unique of Emesis (PUQE-24) Scale questionnaire. The results indicated that the combination intervention of ginger and pomegranate obtained the most significant results from the intervention of ginger and pomegranate intervention with a p value of 0.000